On the Association between Voluntary Disclosure and Earnings Management - Kasznik, Ron (Journal of Accounting Research, 1999)
This study investigates whether managers who issue annual earnings forecasts manage reported earnings toward their forecasts, fearing legal actions by investors and loss of reputation for accuracy. I hypothesize that managers make income-increasing (decreasing) accounting decisions when earnings would otherwise be below (above) management forecasts, and that the earnings management activity is increasing in expected forecast error costs.1 These costs are likely higher for overestimates than for underestimates and are increasing in the magnitude of the forecast